Dendrobium officinale polysaccharide ameliorates polycystic ovary syndrome via regulating butyrate dependent gut–brain–ovary axis mechanism - Feng, Xueping; Wang, Decai; Hu, Linlin; Lu, Haishan; ling, Bo; Huang, Yanna; Jiang, Qinyang (Frontiers in Endocrinology, 2022)
Research has shown that dendrobium officinale polysaccharide (DOP) can promote follicular development and inhibit apoptosis of ovarian granular cells in PCOS rats. However, DOP cannot be absorbed directly by the stomach and small intestine, but is degraded into short-chain fatty acids by gut microbiota in the large intestine and regulated the composition of gut microbiota. How DOP improved ovarian function in PCOS rats through the blood-brain barrier is unclear. In this study, we generated letrozole-induced PCOS rat models and studied the therapeutic effect and mechanism of DOP. The 16S rRNA amplicon sequencing analysis, GC-MS short-chain fatty acids detection and Gene Expression Omnibus database was conducted to screen the significantly changed pathways, and a series of experiments, such as enzyme-linked immunosorbent assay, RT-qPCR, Western blot and immunohistochemical were performed. We found that DOP treatment could improve ovarian morphology and endocrine disorders, restore normal estrus cycle, increase gut microbiota α diversity and alter β diversity, enrichment of butyrate-producing bacterium in PCOS rats. In addition, compared with PCOS rats, those treated with DOP exhibited higher butyrate and polypeptide YY levels, possibly due to the regulation of G protein-coupled receptor 41 expression. These results indicated that DOP relieved the symptoms of PCOS rats which may be related to the mechanism of butyrate dependent gut-brain-ovary axis protection.